Money Multiplication in Islamic Banking – A Discussion on its Impact on Distributive Justice - Omar Javaid (Invest Journal of Sharia & Economic Law, 2023)
This paper explores the legitimacy of the use of Fractional Reserve System in Islamic banking from the normative premise of Islamic economics. The paper uses a methodology of structured literature review and a conceptual analysis of the literature following the approach of Critical Interpretive Synthesis (CIS). The first section of the paper presents the analysis on fractional Reserve Bank (FRB) system, how it leads to multiplication of money supply and influence the long-term inflation and business cycles; the second part of the article explains the extent to which this framework obstructs in the achievement of the objectives of Islamic Economics. This is followed by a reflective analysis of concepts and information gathered from the literature to evaluate how FRB system fits into the fabric of Islamic Economic. The second section of this paper explains how Islamic Banks, with an FRB model and its inclination towards debt-based instruments, would allow Islamic banks to contribute to the problem of inflation, even if they use Musharakah and Mudarabah as a mode of finance.